Assessments of agronomic traits, chemical characteristics, and sensory properties of six albino‐induced yellow tea (Camellia sinensis) cultivars grown in Ningbo, China. Issue 6 (31st May 2022) - Han, Zhen; Fan, Shulei; Jiang, Yanhua; Zhang, Wenbiao; Xu, Yanyang; Wang, Dongmei; Lu, Mengjun
Abstract: Background: Albino‐induced yellow tea is becoming popular in East China because of its special sensory properties. More and more tea gardeners intend to grow albino‐induced yellow tea ( Camellia sinensis ) plants to meet market demand. Results: To help them select the suitable cultivars to grow, agronomic traits (i.e., plant shape, survival rate, plant height, budding density, initial one bud with one leaf development date, albino grade of one bud with three leaves, length of one bud with three leaves, and the cumulative weight of 100 buds), chemical characteristics (i.e., water extract content, tea polyphenols content, free amino acids content, and caffeine content), and sensory evaluation score of six albino‐induced yellow tea cultivars which were introduced and cultivated in Ningbo (a city in East China) were assessed. The principal component analysis (PCA) was used for the comprehensive evaluation. It turned out that the six albino‐induced yellow tea cultivars were with distinguishable agronomic traits, chemical characteristics, and sensory properties. Four principal components were extracted by PCA and the cumulative variance contribution rate reached 96.773%. Among the six cultivars, "Jinguan Tea", "Zhonghuang No.3", and "Yujinxiang" got the top three highest principal component scores. Conclusion: According to the results, albino‐induced yellow tea cultivars which are suitable to be introduced and cultivated in Ningbo, China, are "Jinguan Tea", "Zhonghuang No.3", and "Yujinxiang".